2010
DOI: 10.1097/cej.0b013e32833b48fa
|View full text |Cite
|
Sign up to set email alerts
|

Processed meat and colorectal cancer: a quantitative review of prospective epidemiologic studies

Abstract: A tremendous amount of scientific interest has been generated regarding processed meat consumption and cancer risk. Therefore, to estimate the association between processed meat intake and colorectal cancer (CRC), a meta-analysis of prospective studies was conducted. Twenty-eight prospective studies of processed meat and CRC were identified, of which 20 represented independent nonoverlapping study populations. Summary relative risk estimates (SRREs) for high versus low intake and dose-response relationships we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 54 publications
2
40
1
Order By: Relevance
“…There was little evidence of association between the food groups examined and risk for colorectal cancer: Odds ratios (95% confidence intervals) for a 50 g/day increase were 1.01 (0.84-1.22) for red meat and 0.88 (0.68-1.15) for processed meat [23]. Two other meta-analysis published recently have failed to show any significant association between red meat or processed meat and CRC [24,25]. A very recent systematic review of diet and cancer by Professor Key from Oxford University created a lot of media headlines because of the conclusion that overall, the data do not show a clear association between fruits and vegetables and the risk for colorectal cancer, although they are compatible with a small reduction in risk [26].…”
mentioning
confidence: 94%
“…There was little evidence of association between the food groups examined and risk for colorectal cancer: Odds ratios (95% confidence intervals) for a 50 g/day increase were 1.01 (0.84-1.22) for red meat and 0.88 (0.68-1.15) for processed meat [23]. Two other meta-analysis published recently have failed to show any significant association between red meat or processed meat and CRC [24,25]. A very recent systematic review of diet and cancer by Professor Key from Oxford University created a lot of media headlines because of the conclusion that overall, the data do not show a clear association between fruits and vegetables and the risk for colorectal cancer, although they are compatible with a small reduction in risk [26].…”
mentioning
confidence: 94%
“…The AI consumed significantly more processed meat than NHW women. Processed meat consumption has been reported to increase the risk of development of other gastrointestinal tract cancers such as colorectal cancer, however a recent report showed that this may not be a strong association (Alexander et al, 2010;Miller et al, 2010). The AI had significantly higher BMI than NHW.…”
Section: Discussionmentioning
confidence: 91%
“…This conclusion was received with some criticisms [15,16]. Two meta-analyses of prospective studies concluded that the available epidemiologic data were not sufficient to support an independent and unequivocal positive association [17,18]. The controversy concerned the possible presence of confounding from other lifestyle and dietary factors in the weak magnitude of association and the inconsistency of effect by cancer subsite and gender.…”
Section: Introductionmentioning
confidence: 99%